FENOMENA KESEMPATAN KERJA DI KABUPATEN BOYOLALI DITINJAU DARI SEKTOR INDUSTRI KECIL - Maulidiyah, Maulidiyah; Nuning, Nuning (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2000)
This research focus on the role of small industries as the key sectors for the improvement of village economy, in the purpose of realizing the economic development success in Indonesia. The areas becoming the object of this research is Boyolali regency.The purpose of this research is to find out the description in a general way about the small industrial sectors in Boyolali Regency and the factors which have influences in the small industrial sectors output as well as the small industries ability in giving contribution of thought as the things that can be considered to help another research that has something to do with this issue.In this research there is endogen variable that is the small industries output in Boyolali regency and the eksogen variables that is investment, men power and PDRB.The result of this research shows that investment and PDRB have a positive effect but labor has a negative effect to the small industrial sectors output and also it is found out that the small industry sectors are industries whose capital is incentive so that the effect that it has is in the creating of the small labors. Having that situation, the government has to impose a policy on the use of certain technology in the production process of the small industry sectors to fulfil the creation of new labors.